Mean‐square output consensus of heterogeneous multi‐agent systems with communication noises - Wei Chen; Guojian Ren; Yongguang Yu; Xudong Hai (IET Control Theory & Applications, 2021)
Abstract This paper focuses on the mean‐square output consensus of heterogeneous multi‐agent systems, in which the communication noises are taken into consideration. Through internal model principle and control gain function, the novel state feedback and output feedback control strategies are designed for leaderless and a leader situation respectively to attenuate disturbances caused by communication noises. In addition, based on matrix theory and stochastic analysis, the sufficient condition for output consensus in the corresponding case is obtained. In the end, the simulations are used to confirm the correctness of the conclusion.